Translocation a potential corridor for equine piroplasms in Cape mountain zebra (Equus zebra zebra). (August 2019) - Smith, Rae Marvin; Bhoora, Raksha Vasantrai; Kotzé, Antoinette; Grobler, J. Paul; Lee Dalton, Desiré
Abstract: Translocation of animals in fragmented habitats is an important means of dispersal and gene flow, however, the movement of animals has led to the spread of various diseases globally and wildlife are often the reservoirs of these diseases. Currently, Cape mountain zebra are translocated within South Africa as a management method for augmentation of isolated and fragmented populations. The movement of pathogens due to translocations in local regions have gone largely unchecked, particularly where there may still be isolated regions that can be negatively affected. Equine piroplasmosis is a tick-borne disease caused by Theilaria equi and/or Babesia caballi reported to occur in equids (Bhoora et al., 2010; Zweygarth et al., 2002). Here, the presence of T. equi and B. caballi was detected in 137 clinically healthy Cape mountain zebra from three South African reserves, Mountain Zebra National Park (MZNP), De Hoop Nature Reserve (DHNR) and Karoo National Park (KNP) using the multiplex EP real-time PCR (qPCR) assay. We observed 100% prevalence for T. equi and identified only one animal from MZNP with B. caballi. These results affirm that precautions should be taken prior to founding new populations of Cape mountain zebra and that potential farms and properties adjacent to prospective reserves should be screened for the presence of the organisms in order to mitigate risks of infection to domestic animals. Graphical abstract: Image 1 Highlights: Piroplasms are prevalent in 3 Nature reserves containing Cape mountain zebra. Translocation of Cape mountain zebra leads to risk of spread of equine piroplasms. Equids in adjacent areas to new populations of Cape mountain zebra are at risk of infection.